Impact of Advanced External Beam Radiotherapy on Second Haematological Cancer Risk in Prostate Cancer Survivors. Issue 4 (April 2023) - Jahreiß, M.-C.; Heemsbergen, W.D.; Janus, C.; van de Pol, M.; Dirkx, M.; Dinmohamed, A.G.; Nout, R.A.; Hoogeman, M.; Incrocci, L.; Aben, K.K.H.
Abstract: Aims: External beam radiotherapy (EBRT) for prostate cancer (PCa) has rapidly advanced over the years. Advanced techniques with altered dose distributions may have an impact on second haematological cancer (SHC) risks. We assessed SHC risk after EBRT for PCa and explored whether this risk has changed over the years. Materials and methods: Patients diagnosed with a T1-T3 PCa between 1990 and 2015 were selected from the Netherlands Cancer Registry. Patients treated with EBRT were assigned to EBRT eras based on the date of diagnosis. These eras represented two-dimensional radiotherapy (2D-RT; 1991–1996), three-dimensional conformal radiotherapy (3D-CRT; 1998–2005) or advanced EBRT (2008–2015). Standardised incidence ratios (SIR) and absolute excess risks (AER) were calculated overall and by EBRT era. Sub-hazard ratios (sHRs) were calculated for the comparison of EBRT versus radical prostatectomy and active surveillance. Results: PCa patients with EBRT as the primary treatment ( n = 37 762) had an increased risk of developing a SHC (SIR = 1.20; 95% confidence interval 1.13–1.28) compared with the Dutch male general population. Estimated risks were highest for the 2D-RT era (SIR = 1.32; 95% confidence interval 1.14–1.67) compared with the 3D-CRT era (SIR = 1.16; 95% confidence interval 1.05–1.27) and the advanced EBRT era (SIR = 1.21; 95% confidence interval 1.07–1.36). AER were limited, with about five to six extra cases per 10 000 person-years. Relative risk analysis (EBRT versus radical prostatectomy/active surveillance) showed significant elevation with EBRT versus active surveillance (sHR = 1.17; 95% confidence interval 1.03–1.33; P = 0.017), but not for EBRT versus radical prostatectomy (sHR = 1.08; 95% confidence interval 0.94–1.23; P = 0.281). Conclusion: Increased SHC risks after EBRT for PCa cancer were observed for all EBRT eras compared with the general Dutch male population. Excess risks for EBRT versus other PCa treatment groups were found for only EBRT versus active surveillance. Highlights: Radiotherapy increases the risk of developing a second haematological cancer. Increased risk persists with advanced external beam radiotherapy. Risk-based surveillance for prostate cancer survivors should be considered.